TO INCREASE THE GENERAL PREPAREDNESS OF STUDENTS ENGAGED IN KURASH BY THE METHOD OF CIRCULAR TRAINING - Nuralieva Ugiloy Shomuratovna (European Science Publishing, 2025)
Development of technical and physical training of students engaged in wrestling in a complex-circular training style. Analysis of scientific and methodological literature, pedagogical observations, heart rate monitoring, methods of pedagogical experience All participants must complete a certain number of throws from the hip and back in accordance with the recommended standards in each exercise. In the first month of training, the participant performs 170 scheduled body throws in each method. In total, 510 throws will be made in the first month. With each subsequent month, the number of throws increases by 5% from the previous one and amounts to 537, 564 and 591, respectively. In 4 months of experience, this figure has been brought to an average of 2202 throws. During the pedagogical experiment, there has been steady growth in all registered indicators (see table 3). The motor training density increased by 27.9%, the speed and strength training of students has significantly increased (an increase of 91.7%), the quality of throws from the hip and back by 59.1% and 60%, respectively, dexterity as a complex physical quality increased by 14.6.
Keywords: Month period, indicators of speed and strength training of students, circular training.